2018
DOI: 10.11606/issn.2316-9133.v27i1p59-84
|View full text |Cite
|
Sign up to set email alerts
|

Em meio ao "Vírus" há uma "Pessoa"

Abstract: Neste artigo analiso a história de vida de Luíza, uma jovem mulher e mãe soropositiva, de camadas populares do Rio de Janeiro. Acompanhá-la permitiu compreender uma série de negociações e instâncias existenciais e relacionais que a conforma, que vão desde sua infância, o momento de sua gravidez e embates micropolíticos do dia a dia. Esse texto procurou visibilizar essa interlocutora, lançando mão de perspectivas antropológicas que nos informam ações sociais e a análise fenomenológica do “eu”, da noção de pesso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Over the last 30 years a growing amount of research has shown how structural factors, including gender, race, and class, shape transmission patterns of HIV, the virus that causes AIDS (see Ayres and Ricardo, 1994;Aggleton, 1996;Singer, 1998;Parker and de Camargo, 2000;Parker, 2001;Farmer, 2004;Hunter, 2010;UNAIDS, 2018). One common theme, including in Latin America, is that dominant masculinities that value men's sexual conquests can increase a person's vulnerability to HIV infection both inside and outside marriage (Barbosa, 1999;Santos et al, 2009;Villela and Regina Barbosa, 2017;Monteiro et al, 2016;Agostini et al, 2018;Silva et al, 2014;Hirsch, 2015;Nelvo, 2018). 1 In Brazil, the country of study, the importance of race is demonstrated by National Epidemiological data that reveals particularly high infection rates among Black women (see Villela and Regina Barbosa, 2017;Monteiro et al, 2016;Brazilian Epidemiological Bulletin, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 30 years a growing amount of research has shown how structural factors, including gender, race, and class, shape transmission patterns of HIV, the virus that causes AIDS (see Ayres and Ricardo, 1994;Aggleton, 1996;Singer, 1998;Parker and de Camargo, 2000;Parker, 2001;Farmer, 2004;Hunter, 2010;UNAIDS, 2018). One common theme, including in Latin America, is that dominant masculinities that value men's sexual conquests can increase a person's vulnerability to HIV infection both inside and outside marriage (Barbosa, 1999;Santos et al, 2009;Villela and Regina Barbosa, 2017;Monteiro et al, 2016;Agostini et al, 2018;Silva et al, 2014;Hirsch, 2015;Nelvo, 2018). 1 In Brazil, the country of study, the importance of race is demonstrated by National Epidemiological data that reveals particularly high infection rates among Black women (see Villela and Regina Barbosa, 2017;Monteiro et al, 2016;Brazilian Epidemiological Bulletin, 2020).…”
Section: Introductionmentioning
confidence: 99%